Relationships between energetic, stroke determinants, and velocity in butterfly - Barbosa, T. M.; Keskinen, K. L.; Fernandes, R.; Colaço, P.; Carmo, C.; Vilas-Boas, J. P. (International Journal of Sports Medicine, 2005)
The purpose of this study was to identify the relationship between the bioenergetical and the biomechanical variables (stroke parameters), through a range of swimming velocities, in butterfly stroke. Three male and one female butterflier of international level were submitted to an incremental set of 200-m butterfly swims. The starting velocity was 1.18 m · s-1 for the males and 1.03 m · s-1 for the female swimmer. Thereafter, the velocity was increased by 0.05 m · s-1 after each swim until exhaustion. Cardio-pulmonary and gas exchange parameters were measured breath by breath for each swim to analyze oxygen consumption and other energetic parameters by portable metabolic cart (K4b2, Cosmed, Rome, Italy). A respiratory snorkel and valve system with low hydrodynamic resistance was used to measure pulmonary ventilation and to collect breathing air samples. Blood samples from the ear lobe were collected before and after each swim to analyze blood lactate concentration (YSI 1500 L, Yellow Springs, US). Total energy expenditure (Etot), energetic cost (EC), stroke frequency (SF), stroke length (SL), mean swimming velocity (V), and stroke index (SI) were calculated for each lap and average for each 200-m stage. Correlation coefficients between Etot and V, EC, and SF, as well as between EC and SI were statistically significant. For the relation between EC and SL, only one regression equation presented a correlation coefficient with statistical significance. Relations between SF and V, as well as between SI and V were significant in all of the swimmers. Only two individual regression equations presented statistically significant correlation coefficient values for the relation established between V and the SL. As a conclusion, the present sample of swims demonstrated large inter individual variations concerning the relationships between bioenergetic and biomechanical variables in butterfly stroke. Practitioners should be encouraged to analyze the relationships between V, SF, and SL individually to detect the deflection point in SL in function of swimming velocity to further determine appropriate training intensities when trying to improve EC.